Political resocialization of immigrants 1975-1976 - Immigrants from Finland - Hammar, Tomas (Stockholm University, 1994)
The research project Political Resocialization of Immigrants (PRI) examines political interest and participation among immigrants. The aim of the project was to study immigrant´s relations to community and politics; their living conditions; experiences of immigration to Sweden; factors possible to stimulate increasing political commitment; political attitudes and political behaviour; representatives and demands; information about the Swedish administrative and political system. More than 2 500 interviews were conducted in 1975-1976 with random samples of immigrants born in Finland, Yugoslavia, Poland and Turkey, and a comparison group of Swedish citizens in the 18-67 age group and domiciled in Stockholm municipality. Stratified samples drawn from among the respondents from the first-wave survey were reinterviewed in an election survey during the weeks following the municipal elections of September 1976, in which immigrants participated for the first time. The first-wave interview included questions on: time of moving to Sweden and Stockholm respectively; places of living; language spoken by the respondent, and language spoken by partner and children; newspaper read (Swedish and from native country) and news listened to (Swedish and from other countries); how the respondent would act in a situation when there is a risk of unemployment; circle of friends; organizational membership and activities; knowledge of who to address in Stockholm in different situations; contacts with authorities; important problems in society; interest in Swedish politics; participation in elections in native country and in Sweden; comparison of the personal situation in a number of areas at present and when living in native country; own situation compared with other immigrants and with Swedes respectively; present and earlier occupation; placement in a ´pyramid of society´ in native country and in Sweden; organizational activities of parents; religiosity, own and parents´. In connection with this interview the respondent had to fill in a questionnaire, in which she/he had to state if she/he agreed or not with a number of general statements and a number of statements concerning her/his own nationality. The election survey included questions about election programs in radio and television, study circles discussing the election, information pamphlets, political meetings, knowledge of candidates, voting, important issues in the election campaign, political parties with special interest in issues concerning immigrants, attempts to influence other people how to vote, comparison between Swedish political parties and parties in the native country, interest in election turn-out, and when the respondent decided to vote/not to vote.

Forskningsprojektet Politisk resocialisation av invandrare (PRI) studerar den politiska resocialiseringen av invandrare och politiskt intresse och deltagande från invandrarnas sida. Projektet syftar till att studera invandrares förhållande till samhället och politik; levnadsförhållanden; erfarenheter av invandringen till Sverige; faktorer som kan stimulera ett ökat politiskt engagemang; politiska attityder och politiskt beteende; företrädare och krav; information om det svenska administrativa och politiska systemet. Den första mera omfattande intervjuomgången genomfördes under våren 1975-våren 1976. Bland de som besvarade denna intervju drogs ett nytt urval som intervjuades omedelbart efter valet 1976, det val i vilket invandrare deltog för första gången i Sverige. Den inledande intervjun innehöll bland annat frågor om när man flyttat till Sverige resp. till Stockholm; hur många platser man bott på tidigare; vilka språk man själv talar och vilka språk eventuell make och barn talar; vilka tidningar man läser (svenska resp. från hemlandet) och vilka nyheter man lyssnar på (svenska resp. från andra länder); eget agerande i en situation då det är risk för arbetslöshet; umgänge på fritiden; medlemskap och aktivitet i föreningar; kunskap vart man skall vända sig i Stockholm i olika situationer; kontakter med myndigheter; viktiga samhällsproblem; intresse att följa med vad som händer i svensk politik; deltagande i val i ursprungslandet och i Sverige; jämförelse med situationen nu och i ursprungslandet på ett tiotal områden; egen situation jämförd med andra invandrares resp. svenskars; nuvarande och tidigare sysselsättning, utbildning; placering i samhällspyramiden i ursprungslandet och i Sverige; föräldrars föreningsaktivitet; egen och föräldrars religiositet. I anslutning till denna intervju fick respondenten fylla i en enkät där man bland annat fick ange om man instämde eller ej i ett trettiotal olika allmänna påståenden samt ett antal påståenden som gällde den egna invandrargruppen. Därutöver innehöll enkäten ett antal faktafrågor. Valintervjun innehöll bland annat frågor om vilka valprogram man följt i radio eller TV; om man deltagit i studiekurs om valet; vilka informationsbroschyrer man tagit del av; om man varit på politiskt möte; kandidatkännedom; hur man röstat; viktiga valfrågor; partier som visat särskilt intresse för invandrarfrågor; försök att påverka andra människor hur de skall rösta; jämförelser mellan svenska partier och partier i ursprungslandet; intresse för valutgången; samt när man bestämde sig för hur man skulle rösta resp. att man inte skulle rösta.
Politisk resocialisation av invandrare 1975-1976 - Invandrare från Finland
Keywords: population migration; migration; immigrants; invandrare; Migration; Migration; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Minorities; Minoriteter; Cultural and national identity; Kulturell och nationell identitet; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap